Cefiderocol: An Overview of Its in-vitro and in-vivo Activity and Underlying Resistant Mechanisms - Yao, Jiahui; Wang, Jin; Chen, Mengli; Cai, Yun (Frontiers in Medicine, 2021)
Treatment of multidrug-resistant (MDR) Gram-negative bacteria (GNB) infections has led to a global public health challenging because of the bacterial resistance and limited choices of antibiotics. Cefiderocol (CFDC), a novel siderophore cephalosporin possessed unique drug -delivery systems and stability to β-lactamases, has the potential to become first-line therapy for most aggressive MDR Gram-negative pathogens infection. However, there have been reports of drug resistance in the course of using CFDC. This review provides an overview of the in vitro and in vivo activity of CFDC and potential resistance mechanism of it were summarized. In general, CFDC shows excellent activity against a broad range of MDR GNB pathogens, including Enterobacteriaceae, Klebsiella pneumoniae, Pseudomonas aeruginosa, Acinetobacter baumannii, and Stenotrophomonas maltophilia. The expressions of metallo-β-lactamases, such as inosine-5’-monophosphate (IMP), Verona integron-mediated metallo-β-lactamase (VIM), and New Delhi metallo-β-lactamase (NDM) are associated with a higher resistance rate of CFDC. Carbapenem resistant phenotype has little effect on the resiatance rate, although the acquisition of a particular carbapenemase may affects cefiderocol susceptibility of the pathogens. For potential resistance mechanism, mutations in β-lactamases and TonB-dependant receptors, which assist CFDC entering bacteria, would increase the minimum inhibitory concentration (MIC) value of CFDC against MDR pathogens. Since the development of CFDC resistance during its utilization has been reported, prudent clinical applications are still necessary to preserve the activity of CFDC.